Hydrocephalus in Guillain barre syndrome: A case report and review of the literature - Abdulaziz, Ammar Taha Abdullah (Medicine (Baltimore), 2020)
RATIONALE: Guillian-Barré syndrome (GBS) is a devastating autoimmune disorder characterized by progressive ascending weakness, areflexia with or without autonomic and sensory disturbances. Hydrocephalus is a rare but well-documented complication in patients with GBS. However, due to the rarity of this condition, no treatment guideline for GBS with hydrocephalus is currently available. PATIENT CONCERNS: We describe a 23-year old woman with a history of bilateral limbs pain followed by dysarthria, dysphagia, severe quadriplegia 0/5, areflexia, loss of consciousness and dysautonomia. Neuroimaging studies revealed enlarged lateral ventricles; while Electromyography demonstrated demyelination and nerve injury. Lumbar puncture results showed elevated protein level 2.6 g/L; normal glucose and cell count. DIAGNOSIS: GBS with hydrocephalus. INTERVENTIONS: The patient was started on intravenous immunoglobulin for 5 consecutive days followed by endotracheal intubation and supportive therapy including osmotherapy and CSF drainage. OUTCOMES: At 2 months after admission, the patient stopped choking and had a significant improvement in muscles’ strength (grade 4) and pain; then was discharged. On 1 year post-discharge follow-up, CT has revealed a significant improvement of hydrocephalus, and the patient has completely returned to the normal baseline. LESSONS: Respiratory failure is the strongest predictor of concurrent hydrocephalus in patients with GBS. The prognosis of hydrocephalus in patients with GBS is usually good, and it can be medically treated; thereby shunt surgery is rarely required.